(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article considers the issue of modern trends in the placement of household service enterprises in modern conditions. The analysis shows that the principles of the development of the network of household service enterprises in the areas of new buildings have changed, as well as the need to improve approaches to the planning of retail and household infrastructure of residential areas. According to the results of the survey, the author studied the factors affecting the behavior of consumers of individual services.